THE EVOLUTION OF CLOUD COMPUTING POLICIES IN EMERGING ECONOMIES: A COMPARATIVE STUDY OF PAKISTAN AND INDIA - Laviza Asif Memon; Naeem Akbar Channar; Muhammad Kashan Surahio; Maheen Mahwish Surhio (Spectrum of Engineering Sciences, 2025)
Cloud computing has redefined IT resource alloca- tion by empowering on-demand access to computational capacity, data storage, and software applications by means of the Internet without the need for expensive infrastructure. Countries have de- veloped cloud management policies in order to improve economic development, guarantee information security, stimulate foreign investment, and mitigate regulatory uncertainties. The purpose of this study is to examine the development of cloud policies implemented in developing countries, centering on Pakistan and India. Hence, examining the differences in cloud infrastructure, data security strategies and regulatory frameworks between these two countries. This study also explores the effect of these policies on startups, businesses, foreign investment and international race. This research also examines key issues, for example policy execu- tion, data confidentiality, and processing methods by reviewing government policy documents. The results show that the India has employed advanced laws supporting innovative technology and strong data security policies. In contrast, Pakistan is experiencing a gap in comprehensive structure, although it is still developing its regulatory framework. This research determines the root cause of these differences and their impact on the customer rights and business operations. In conclusion, recommendations are provided for both countries to strengthen cloud policies by addressing regulatory gaps, improving compliance with inter- national standards, and enhancing data security frameworks. In order to strengthen cloud policies in both countries by addressing regulatory gaps, enhancing compliance with international stan- dards, regulations and data security frameworks. The results of this research will help guide the development of the regulatory landscape of cloud computing, especially in both countries.